Human Nervous/Endocrine System and Unplugged CT Teaching Approach - Aytekin, Aydan; Topcu, Mustafa Sami (WILEY, 2026)
The human nervous and endocrine systems are challenging science topics for students because of their abstract and complex structures. In particular, the electrical and chemical transmission processes between nerve cells occur at the microscopic level, making them difficult for students to observe directly. For this reason, incorporating computational thinking (CT), a key STEM skill, is considered important in teaching such abstract biological processes. This study aimed to develop unplugged CT-integrated activities for teaching the human nervous and endocrine systems and to support the conceptual learning of sixth-grade students (aged 11-12). A quasi-experimental design was employed with 60 sixth-grade students from a public middle school. The intervention was implemented over a three-week period, consisting of 12 class hours (40 min per class hour). The findings indicated that unplugged CT activities significantly supported students' understanding of concepts related to the human nervous and endocrine systems. In addition, students reported that the activities were engaging and helped them better understand the mechanisms of these systems. Overall, the results suggest that integrating CT into science education-particularly in life sciences, where abstract and complex concepts are common-can enhance learning environments and increase students' interest in STEM fields.
Keywords: COMPUTATIONAL THINKING; MATHEMATICS; EDUCATION; K-12; Education & Educational Research